Enhanced H3K4me3 demethylation by inhibition of fatty acid oxidation enables heart regeneration in adult mice - Li, Xiang; Justus Liebig University Giessen (My University, 2021)
During early postnatal heart development, the metabolic profile switches from glycolysis to fatty acid oxidation (FAO). At the same time, cardiomyocytes (CM) undergo profound maturation characterized by hypertrophic growth, cytoarchitectural remodeling, chromatin reconfiguration, and cell cycle withdrawal. The subsequent structural and functional alterations in mature CM indicate synergistic rewiring of transcriptional networks regulated by epigenetic mechanisms in combination with environmental and metabolic signals. Recent studies of cellular metabolism demonstrated that metabolites derived from various metabolic pathways function as cofactors or substrates for distinct epigenetic modifiers, thereby coupling chromatin-dependent gene regulation with the metabolic state. To gain a deeper insight into the interplay between epigenetic processes and metabolic pathways during cardiac development, maturation, and heart regeneration, I prevented metabolic maturation by cardiomyocyte-specific inactivation of CPT1B, a crucial enzyme for FAO. Cpt1b inactivation led to cardiomegaly and attenuated cardiac damage after myocardial injury due to augmented CM proliferation and enhanced resistance to ischemic injury. Interestingly, FAO inhibition after the loss of Cpt1b did not reduce the intracellular level of acetyl-CoA, which is an essential metabolite mainly produced by FAO, due to enhanced metabolic compensation from glucose and amino acids. In contrast, Cpt1b inactivation led to marked accumulation of αKG, caused by increased generation but decreased consumption. Excessive αKG was sensed by KDM5, leading to demethylation of cell-specific broad H3K4me3 peaks located in promoters of key genes driving cardiac development. Demethylation of H3K4me3 reduced expression of cardiac maturation genes, converting cardiomyocytes to a more immature, proliferation-competent state. Overall, the results obtained for the thesis uncover a complex interplay between epigenetics and metabolic pathways for regulating the maintenance of CM maturity and cell cycle arrest. The study identifies mitochondrial oxidative metabolism as an attractive target to treat heart failure. Manipulation of metabolic processes were found to alter epigenetic events in the nucleus, which was exploited to regenerate diseased hearts. Furthermore, my research uncovered that KDM5 senses metabolic cues to deactivate crucial cardiac maturation genes, which offers new perspectives to treat heart diseases.
Keywords: Metabolism; Epigenetics; Heart regeneration; ddc:570